Kecerdasan Emosional Bidan Desa serta Kaitannya dengan Kinerja Mereka dalam Pelaksanaan Tugas - Notosiswoyo, Mulyono (Jurnal Kedokteran YARSI, 2008)
The midwives have an importance role in lowering death rate of giving birth women. Therefore, it is necessary for them to have the optimal performance on their duty. On the other hand, Emotional Quotient is the capability to motivate themselves, hold not to be frustrated, arrange sense of filling, an empathy and to prevent of stress in order to maintain their thought capability, and to keep human relation. This study was aimed to find out the performance of the midwives in their duty, their Emotional Quotient, and correlation between them. The population studied was a group of midwives working in Bogor in 2004. A number of 70 midwives was purposively selected fulfilling two criteria i.e. at least one year experience and voluntarily available to join the study. Variable of performance included capability to care pregnant women, post partum women, helping to give birth to and to lead the traditional midwives. The study showed that 48.6% of the midwives had high performance, and 41.4% had sufficient performance. Meanwhile, their Emotional Quotient, were 38.6% sufficient, but some of them (34.3%) showed high Emotional Quotient. Furthermore, there was a positive correlation between performance and Emotional Quotient of the midwives. The higher the Emotional Quotient, the higher their performance or 18.2% of their performance was determined by their Emotional Quotient.